Pengaruh Kombinasi Tepung Ikan Sepat Siam (Trichogaster pectoralis) dan Tepung Terigu Terhadap Karakteristik Sensori dan Fisiko-Kimia Mantou - Partha Aryani; Rodiana Nopianti; Indah Widiastuti (Universitas Sriwijaya, 2018)
The purpose of this research was to determine the effect of combinations of fish meal and wheat flour to physicochemical and sensory of mantou. This research used a randomized block design consisted of one-factor treatment with three replications. Factor treatment consists of combinations fish meal and wheat flour 0 g : 100 g, 10 g : 90 g, 20 g : 80 g, 30 g : 70 g, 40 g : 60 g and 50g : 50 g. The parameters observed were physical characteristics (percentage level of development of bread, texture, and Whiteness), chemical characteristics (moisture content, ash, protein, lipid, carbohydrate, calcium and phosphor) and sensory characteristics (color, flavor, aroma, and texture). Result of this research showed that average value percentage level of development mantou were 3.49 to 1.85, texture was 661.53 gf to 1307.13 gf, whiteness was 63.32% to 51.20% moisture content were 35.92% to 30.79%, ash content was 1.73% to 3.99%, protein was 11.20% to 26.75%, lipid was 3.51% to 7.26%, carbohydrate was 47.64% to 31.21%, calcium was 7.21 mg/100g to 25.21 mg/100g, phosphor were 53.54 mg/100g to 51.53 mg/100g, and a sensory test had significantly (Fhitung>Ftabel) for color, flavor, aroma, and texture. The best treatments according to sensory characteristics were 20% of the fish meal.